2003
DOI: 10.1159/000073514
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal and Postnatal Contents of Amino Acid Neurotransmitters in Mouse Parietal Cortex

Abstract: This study documents the variation in the amino acid neurotransmitter contents during mouse parietal cortex development, from embryonic day 13 (E13) until young adulthood, between postnatal day 21 (P21) and P30. Taurine, an inhibitory neurotransmitter and neuromodulator, is the most abundant neurotransmitter in the developing neocortex, whereas, at the adult stage, glutamate is the more prominent neurotransmitter playing an excitatory role, and GABA is the major inhibitory neurotransmitter. During the prolifer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
48
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(52 citation statements)
references
References 66 publications
3
48
0
1
Order By: Relevance
“…In addition to the coexistence of Glu and GABA, consistent with previous studies reporting age-dependent changes in multiple neurotransmitter systems in brain tissue (36,37), we also found that the concentrations of amino acids neurotransmitters, including Glu and GABA, in single cells decrease with age. Interestingly, we observed that the correlation among single-cellular Gln, Glu, and GABA is much more significant in infants than that in children or adolescents.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In addition to the coexistence of Glu and GABA, consistent with previous studies reporting age-dependent changes in multiple neurotransmitter systems in brain tissue (36,37), we also found that the concentrations of amino acids neurotransmitters, including Glu and GABA, in single cells decrease with age. Interestingly, we observed that the correlation among single-cellular Gln, Glu, and GABA is much more significant in infants than that in children or adolescents.…”
Section: Discussionsupporting
confidence: 91%
“…( Changes in the Levels of Cytoplasmic Chemical Constituents at Different Stages of Brain Development. Previous reports suggest that the levels of amino acid neurotransmitters tend to decrease with age (36,37). Using single-cell MS, we investigated this idea at the single-neuron level.…”
Section: Concentrations Of Cytoplasmic Chemical Constituents In Singlmentioning
confidence: 99%
“…Like for NAAG, the highest glycine concentrations in the brain are observed at P10 and decline until adulthood (Kulak et al, 2010). In fact, the rate of glycine synthesis peaks around 10-15 days after birth (Benítez-Diaz et al, 2003;Lahoya et al, 1980) and likewise, during this period, glycine receptors undergo a major switch of the relative expression of glycinergic subunits (Lynch, 2004). It is interesting to note that the increase in levels of excitatory neurotransmitters, glutamate and aspartate (NMDA receptor agonists), is paralleled by a reduction in the concentration of its modulator NAAG as well as its co-agonist glycine.…”
Section: Neurotransmitter Metabolismmentioning
confidence: 98%
“…To assess the physiological relevance of the pathway described above, we look to the possibility of physiological activators of the Na ϩ channel in PP cells. Glycine and͞or taurine appear as potential candidates because they are abundantly present in embryonic neocortex (7,25), together with their target receptor, the GlyR (25). Activation of GlyRs during embryonic stages is excitatory, leading to membrane depolarization (25), which can, in turn, activate Na ϩ channels.…”
Section: Taurine and Glycine Acting On Glycine Receptors (Glyrs) Are mentioning
confidence: 99%
“…GABA and glutamate are both present in the neocortical wall and can regulate neuronal progenitor proliferation (4,5) and neuronal migration (6). Taurine and glycine are also present and have been reported to be the most abundant neurotransmitters at E13 in mouse neocortex (7). Little is known about the channels and pathways that are involved in this early activity, and particularly little is known about how these neurotransmitters are secreted before the appearance of voltage-dependent Ca 2ϩ channels (8,9).…”
mentioning
confidence: 99%